2005
DOI: 10.1371/journal.pgen.0030218.eor
|View full text |Cite
|
Sign up to set email alerts
|

A RNA interference screen identifies the Protein Phosphatase 2A subunit PR55γ as a stress-sensitive inhibitor of c-SRC

Abstract: Protein Phosphatase type 2A (PP2A) represents a family of holoenzyme complexes with diverse biological activities. Specific holoenzyme complexes are thought to be deregulated during oncogenic transformation and oncogeneinduced signaling. Since most studies on the role of this phosphatase family have relied on the use of generic PP2A inhibitors, the contribution of individual PP2A holoenzyme complexes in PP2A-controlled signaling pathways is largely unclear. To gain insight into this, we have constructed a set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…However, it is intriguing that they could still partially transduce the E4orf4 toxic signal. It has been previously reported that knockdown of various B55 subunits led to stress-induced Src activation (49). Src is another major E4orf4 partner that contributes to E4orf4-induced cell death, and E4orf4 was shown to affect Src activity independently of its interaction with PP2A (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is intriguing that they could still partially transduce the E4orf4 toxic signal. It has been previously reported that knockdown of various B55 subunits led to stress-induced Src activation (49). Src is another major E4orf4 partner that contributes to E4orf4-induced cell death, and E4orf4 was shown to affect Src activity independently of its interaction with PP2A (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…PP2A has been shown to dephosphorylate and therefore inhibit Src, a non-receptor tyrosine kinase that has been shown to mediate TRAIL resistance in breast cancer cells via activation of Akt pathway survival signaling. 102,103 Using the BT549 breast cancer cell line, Xu et al demonstrated that TRAIL signaling activated Src, which in turn phosphorylated caspase-8, initiating apoptosis. 104 Using immunoprecipitation, they found that TRAIL stimulation led to increased PP2A dephosphorylation of Src, abrogating Src-mediated activation of caspase-8.…”
Section: Breast Cancermentioning
confidence: 99%
“…We chose PP2A because PP2A has been shown to target the holoenzyme to dephosphorylate Src at serine 12, a site that is important for c-Src activation upon cell stress (28). To this end, HEK293T cells co-transfected with pcDNA3-Src, PP2A/C-HA (catalytic subunit of PP2A), and caspase-8-HA were left untreated or treated with TRAIL and then harvested for Western IP.…”
Section: Src Associates With the Catalytic Subunit Of Pp2a Phosphatasmentioning
confidence: 99%
“…Protein phosphatase 2A (PP2A) is the major serine-threonine phosphatase that regulates a number of cell signaling pathways (28). PP2A is a trimeric holoenzyme that consists of a catalytic subunit, a structural subunit, and a regulatory subunit (29).…”
mentioning
confidence: 99%